Effect of pore geometry on the fatigue properties and cell affinity of porous titanium scaffolds fabricated by selective laser melting. (December 2018) - Zhao, Danlei; Huang, Yutian; Ao, Yong; Han, Changjun; Wang, Qian; Li, Yan; Liu, Jie; Wei, Qingsong; Zhang, Zhen
Abstract: Porous titanium scaffolds with different unit cell type (tetrahedron and octahedron) and pore size (500 µm and 1000 µm) were fabricated by selective laser melting (SLM), and the effects of unit cell type and pore size on their fatigue properties and cell affinity were studied. The fatigue properties were performed by static and dynamic mechanical testing, while the cell affinity was evaluated in vitro with mouse osteoblast cells. It was found that octahedron scaffolds exhibited superior static mechanical properties, longer fatigue lives and higher fatigue strength in comparison to those of tetrahedron ones. As expected, scaffolds with 1000 µm pore resulted in lower compressive properties and shorter fatigue lives compared to those with 500 µm pore. The differences were analyzed based on the unit cell structure, porosity, and manufacturing imperfections. Scanning electron microscopy (SEM) and immunofluorescence showed that cells spread better on octahedron scaffolds than those on tetrahedron ones. Meanwhile, the scaffolds with 1000 µm pore were more suitable for cell attachment and growth within the same unit cell owing to higher porosity. The comparison of different pore geometry on the mechanical and biological property provided further insight into designing an optimal porous scaffold. Graphical abstract: Highlights: The unit cell and pore size were estimated to affect the fatigue behavior and cell affinity of porous titanium scaffolds. Octahedral scaffolds perform better than tetrahedral ﻿o﻿n﻿e﻿s in fatigue properties ﻿th﻿a﻿t﻿ increase with decreasing pore size. Cell proliferation was superior in the lattices with bigger pore size, and specifically in the octahedral unit cell.